DEVELOPMENT OF TREAD ON THE BASIS OF COLOR ALLOYS RECYCLED IRON-CARBON ALLOYS PROTECTION FROM CORROSION - A. A. Pivovarchyk; V. D. Povidajko; A. M. Mikhaltsov (Литьë и металлургия)
The results of development of the compositions of protectors for the corrosion protection low-carbon alloys used in the automotive industry, using as the raw material of the secondary aluminum raw materials. The results of research on the effectiveness of the tread designed to protect the alloy composition.